Sustainability assessment of new construction technologies : a comparative case study - Gervásio, H. (2005)
In the framework of mixed building technology, different construction methods and materials are combined in the same building, allowing structures to achieve higher quality, safety, economy and to improve sustainability. Buildings are one of the major concerns regarding the sustainability of our habitat. Construction industry consumes materials and energy and is one of the main causes of pollution and resource depletion. The use of environmentally friendly materials and cleaner construction methodologies are a major step towards the well being of the environment and foster sustainable development. In this paper the results of a comparative analysis, in view of a sustainable development, conducted upon a typical residential floor plan of a family-house located in Algarve, south of Portugal, is presented. © 2005 Taylor & Francis Group.